509 A biochemical approach to atrial fibrillation in older patients. (8th December 2021) - Ricciardi, Giulia; Pieraccini, Giuseppe; Di Serio, Claudia; La Marca, Giancarlo; Fumagalli, Stefano
Abstract: Aims: Atrial fibrillation (AF) is the most common arrhythmia among the elderly. It is characterized by a disordered electrical activity of the atria and is associated with increased morbidity and mortality. The pathogenesis of AF is not completely understood as it depends on a multifactorial combination of electrical and structural remodelling and inflammation. Metabolomics is the study of the small molecules present in a given biological sample and it has been widely used to determine the metabolic signatures of certain diseases. Untargeted metabolomics consists of a comprehensive screening of all measurable metabolites to identify patterns related to a certain disease, while targeted metabolomics aims at analysing a defined group of metabolites belonging to a specific metabolic pathway or class of compounds. Mass spectrometry (MS), coupled with gas chromatography (GC) and liquid chromatography (LC) offers the possibility of performing quantitative analyses with high selectivity and sensitivity. Aims of this project were to understand the biomolecular mechanisms underlying the onset of AF. Methods: We compared plasma samples of older patients with AF with those of healthy subjects. We started from untargeted metabolomics to explore the whole metabolome; then we focused on the lipidomic profile, and, finally, we measured the plasma concentration of acylcarnitines and some amino acids, known to be diagnostic markers of certain metabolic diseases. Fifty patients (age: 76 ± 6 years) and 26 healthy subjects (age: 65 ±19 years) were recruited for the study. A blood sample was drawn by each patient. Samples for metabolomics and lipidomics were processed, respectively, with a GC-MS platform and with high-resolution LC-MS. Results: Differences in diseased and healthy metabolomic and lipidomic profiles were not detected, while the concentration of some acylcarnitines and amino acids resulted to be significantly different in the two groups. In particular, two long-chain acylcarnitines (LCACs), C14 and C18:1, were more abundant in the plasma of AF patients, while glycine, which has scavenger properties, had a lower concentration. High levels of circulating LCACs have been associated with cardiovascular diseases and they are known to alter the heart electrophysiology, thus representing a possible marker of the development of arrhythmias. We can hypothesize that the different concentrations we found possibly reflect a higher oxidative and metabolic stress induced by the arrhythmia. Conclusions: The alterations of the LCACs we found in AF patients could represent the basis to guide specific therapeutic interventions aimed at reducing the incidence of the hemodynamic and embolic complications of the arrhythmia. In particular, recent guidelines for the management of AF patients introduced the acronym ABC, which means 'Avoid stroke'—A, 'Better symptoms management'—B, and 'Cardiovascular risk and comorbidity management'—C. In this sense, the present research represents an attempt to join and enrich the traditional clinical approach with data derived from laboratory activity, to improve the outcome of the oldest segment of cardiac patients, often presenting rhythm alterations.